(3RgQ GdQHjYs - (3GdLRGFQj, GdLRGFQj, fYeI Gddg Hf YHO Gddg Hf eMeO GdMSjfj, J (B1112(3g` (B1701(3es
(3ChdgG (B:s
(3ChdgG(B: (3aUd(B: (3bGd GdbGVj aj QGFjI GdJSJQj(B: (3KQGg hai YRe Edi eG gh GdMb aj (B.. (3NdGaI GdKdGKjf hfXGFQgs
(3BNQgG (B:s
(3BNQgG(B: (3aj hajGJ GdYdeGA HYO PcQ JGQjN HdhZg ceG PcQ bGd(B: (3ohLO HNW hdOg UGdM(B: (3Jhaj hGdOj eMeO Hf EOQjS jhe GdLeYI hbJ GdXgQ KGef YTQ ThGd SfI KeGf hYTQjf hJSY eFIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B8: 39s
(3GdPQjYI, L (B12: 50s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdeYGQa GdYGeIs